Inert Knowledge in Tertiary Teacher Training and How to Activate it - Hoa, Nguyễn Thị Phương; Hương, Nguyễn Thanh (VNU Journal of Science: Education Research; Vol 31 No 4, 2015)
The progress of the education development in Vietnam is impressive as recently shown in the very successful performance of Vietnamese students of the last PISA round. On the other hand the problems are still tremendous, above all in tertiary teacher training: many colleges and pedagogic universities are under-equipped, their scientific level is poor and their ability to carry out effective reform steps is low. In this situation it is stunning, that the approach of A ction Research is still so undervalued in Vietnamese colleges and universities The approach of Action Research is an established strategy that aims on behavioral change by systematic self reflection and do not need expensive financial means nor highly qualified personnel. The article presents a reform strategy which avoids detailed external defaults and motivates the persons directly involved to put into practice self directed new teaching/learning schemes instead. This self learning by doing promises very effective results as they are based on the direct experience of individuals and groups. To promote the sustainability of this learning scheme and to foster the scientific skills of the participants at the same time the necessary reflection must be conducted by simple means of and according to systematic research. Learning by practising science - even in a simple way - means to join the most effective way of sustainable learning human civilisation has developed: learning systematically according to basal scientific principles. An additional appeal occurs out of the fact that this plan can be realized under the poor conditions of many Vietnamese colleges and universities, that it takes into consideration the particular preconditions in situ and that it tends to establish an enlarging new learning culture.